Feature Papers of Drones Vol. 2 - Gonzalez-Aguilera, Diego; Rodríguez-Gonzálvez, Pablo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint compiles the articles, communications, and review articles from top researchers describing novel or new cutting-edge designs, developments, and/or applications of unmanned vehicles. This reprint encompasses the key topics related to drone design, communications as well as autonomous Flight and Navigation. Special attention is paid to the drones' applications to environmental and earth sciences, including in agriculture, forestry, water, and marine environments; other innovative applications are also explored including in relation to the field of application, such as the inclusion of new deep learning techniques.